Access improvement using lean healthcare for radiation treatment in a public hospital - Pinto, Carlos Frederico [UNESP]; Coelho, Stela Maris [UNESP]; Calado, Robisom Damasceno [UNESP]; Silva, Messias Borges [UNESP] (My University, 2013)
Radiation treatment for cancer in Brazil faces huge access restrictions due limited resources and poor assistance design. Radiation treatment access waiting time can be as long as seven months. The purpose of this report is to show how lean thinking can be applied to healthcare by using lean methods. The case study/report presented describes how processes were improved using Lean Value Stream Mapping tools and Queue Theory tools. Major outcomes were focused on reducing waiting time to patient access to radiation treatment and to reducing daily waiting time to access to treatment slots. The performance improvement was in the order of 75% to treatment slots access, reducing from two hours to 30 minutes; and access to care waiting time reduced from more than three months to same day access to special cases; and one week waiting time or planned access to all other. The process redesign also eliminated up to three hours of overtime daily. © IFAC.
Keywords: Lean Manufacturing; Production Control; Queues.